2014
DOI: 10.4081/jlimnol.2014.920
|View full text |Cite
|
Sign up to set email alerts
|

Daphnia lumholtzi Sars, 1885 (Cladocera: Daphniidae) invades Argentina

Abstract: The extent of freshwater biological invasions is difficult to predict.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…Daphnia found in the study also have a varying distribution with species number changing latitudinally across regions, and follows a trend which has been analyzed in a recent study by Popova and Kotov (2013). D. (C.) lumholtzi is distributed in Africa, Asia and Australia but recently spread to North America (Benzie, 2005;Sorensen and Sterner, 1992) and South America (Kotov and Taylor, 2014). D. (C.) similoides extends from the Indian subcontinent to Central China (Hudec, 1991;Benzie, 2005) but recently it has been shown that China houses a distinct sub-species, D. (C.) similoides sinensis (Gu et al, 2013).…”
Section: Discussionsupporting
confidence: 75%
“…Daphnia found in the study also have a varying distribution with species number changing latitudinally across regions, and follows a trend which has been analyzed in a recent study by Popova and Kotov (2013). D. (C.) lumholtzi is distributed in Africa, Asia and Australia but recently spread to North America (Benzie, 2005;Sorensen and Sterner, 1992) and South America (Kotov and Taylor, 2014). D. (C.) similoides extends from the Indian subcontinent to Central China (Hudec, 1991;Benzie, 2005) but recently it has been shown that China houses a distinct sub-species, D. (C.) similoides sinensis (Gu et al, 2013).…”
Section: Discussionsupporting
confidence: 75%
“…Perhaps the most successive invader is D. lumholtzi Sars, 1885, which was introduced together with African blue tilapia or/and nile perch to southern USA (Sorensen and Sterner, 1992), and which has now colonized all of the USA (Benson et al, 2013), Mexico (Elias-Gutierrez et al, 2008), Brazil (Zanata et al, 2003) and Argentina (Kotov and Taylor, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The genetic similarity found between populations from the American continents suggests that Brazilian specimens are genetically similar to native populations from Africa and/or Asia. Kotov and Taylor () suggested that the populations they found in Argentina may be an expansion of Brazilian populations from the Upper Paraná River. Although these authors did not publish any of their studied sequences, our genetic sequence showed the same haplotype found in specimens from Arkansas, United States, which had a sequence similar to that of Argentinian populations.…”
Section: Discussionmentioning
confidence: 99%
“…The species was first recorded in Brazilian waters in 2000 (Zanata, Espíndola, Rocha, & Pereira, ) and was recorded in Mexico in 2008 (Elías‐Gutiérrez, Jerónimo, Ivanova, Valdez‐Moreno, & Hebert, ). In 2003, this species was found in the Upper Paraná River floodplain (Simões et al, ) and 3 years later was recorded in the Lower Paraná River, in the Argentinian stretch (Kotov & Taylor, ) (Figure ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation